GONGRONEMA LATIFOLIUM DELAYS GASTRIC EMPTYING OF SEMI-SOLID MEALS IN DIABETIC DOGS. - ogbu, sylvester osita; Agwu, Kenneth Kalu; Asuzu, Isaac Uzoma (African Journal of Traditional, Complementary and Alternative Medicines, 2013)
ABSTRACTThe aim of the study was to investigate sonographically the effect of Gonogronema latifolium on gastric emptying of semi-solid meals in diabetic dogs. Twenty-five alloxan-induced diabetic dogs were randomly allotted into five groups of five dogs each in a randomized placebo-controlled study. These are placebo, prokinetic dose, low dose, moderate dose and high dose groups. The placebo group served as the control. The low, moderate and high dose groups ingested methanolic leaf extract of G. latifolium at 100 mg/kg, 250 mg/kg, 500 mg/kg respectively while the prokinetic group ingested 0.5 mg/kg of metoclopramide. After a 12- hour fast, each group ingested its treatment capsules 30 minutes before the administration of test meal. Measurements of gastric emptying and blood glucose levels were obtained from each dog 30 minutes before and immediately after the ingestion of a test meal, every 15 minutes for another 4 hours and then every 30 minutes for further 2 hours. Gastric emptying of the moderate and high dose groups were 227.8 ± 9.9 min and 261.3 ± 19.3 min respectively and significantly (p < 0.0001) slower than the placebo control group of 143.0 ±17.8 min. The gastric emptying of the low dose group (169.8 ± 3.8) and control group did not differ significantly (p > 0.05). A strong inverse relationship between gastric emptying and the incremental blood glucose levels was noted in the diabetic dogs after the ingestion of Gonogronema latifolium (r = - 0.90; p < 0.0001). Gonogronema latifolium delayed gastric emptying in diabetic dogs.